2021
DOI: 10.1186/s13011-021-00395-6
|View full text |Cite
|
Sign up to set email alerts
|

The impact of COVID-19 on healthcare delivery for people who use opioids: a scoping review

Abstract: Research objective The COVID-19 pandemic disrupted healthcare delivery worldwide with likely negative effects on people who use opioids (PWUO). This scoping review of the original research literature describes the impact of the COVID-19 pandemic on healthcare delivery for PWUO and identifies gaps in the literature. Methods This scoping review of the original research literature maps the available knowledge regarding the impact of the COVID-19 pande… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 35 publications
1
21
0
Order By: Relevance
“…Our study provides a characterization of evidence regarding the impacts of the COVID-19 pandemic on a comprehensive range of outcomes concerning illicit substance use within US-specific contexts over the first two waves. Other scoping reviews that shared similar goals have either presented generalized global findings [ 16 ] or were narrowed in scope to specific outcomes or study populations (i.e., opioid use-related disorders only) [ 14 , 15 , 17 ]. Our findings address more discrete research questions to rigorously characterize and complement the evidence (through full data extraction provided in Appendix A–C) and guide subsequent research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study provides a characterization of evidence regarding the impacts of the COVID-19 pandemic on a comprehensive range of outcomes concerning illicit substance use within US-specific contexts over the first two waves. Other scoping reviews that shared similar goals have either presented generalized global findings [ 16 ] or were narrowed in scope to specific outcomes or study populations (i.e., opioid use-related disorders only) [ 14 , 15 , 17 ]. Our findings address more discrete research questions to rigorously characterize and complement the evidence (through full data extraction provided in Appendix A–C) and guide subsequent research.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas previous review articles have examined various interactions between the COVID-19 pandemic and substance use in the US [ 14 , 15 , 16 , 17 ], none have sought to systematically synthesize and appraise the quantitative evidence that emerged during the midst of this crisis on the impact of key changes in individual and structural level determinants of substance use risk and their associated health outcomes. A rigorous approach is therefore needed to describe it and support the formulation of unbiased inferences, particularly with regards to the priorities for future research and the implications for policymakers in responding to similar crises in the future within US communities.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that people may seek forums and self-help groups to provide emotional support [ 39 - 42 ], particularly given online forums may allow anonymous disclosure without feelings of shame or guilt [ 43 ]. Finding emotional support without being stigmatized is especially relevant for PWUD [ 44 ] and is an urgent matter, given opioid overdose–related use of health care has increased throughout the pandemic. Future research should examine subgroups of PWUO who may be at heightened risk for reduced access to care during the pandemic [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finding emotional support without being stigmatized is especially relevant for PWUD [ 44 ] and is an urgent matter, given opioid overdose–related use of health care has increased throughout the pandemic. Future research should examine subgroups of PWUO who may be at heightened risk for reduced access to care during the pandemic [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Telemedicine has been increasingly described as a solution for improving access to OUD treatment, and there is a growing body of research on the use of telemedicine during the pandemic and beyond [ 35 ]. Treatment initiation via telemedicine was found to increase access to treatment from home using buprenorphine [ 36 ]. However, more research is needed to understand whether there is variation in the use of telemedicine across race/ethnicity groups that could result in disparities.…”
Section: Discussionmentioning
confidence: 99%